Development of Jam Product from Peel and Flesh of Dragon Fruit as High Antioxidant Snack - Nisa, Tessa Chairun; Marjan, Avliya Quratul; Nasrullah, Nanang (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
This study aims to determine the effect of different proportion of peel and flesh red dragon fruit of the jam to organoleptic test, to obtain the results of analysis of chemical properties and physical properties of jam, and also the selected formula. This research used experimental method by using Randomized Design. The organoleptic test was then analyzed using Kruskal Wallis and Mann-Whitney method. The result showed that proportion of peel and flesh of red dragon fruit has significant test (p<0,005) on hedonic quality test of color, texture, taste, aftertaste and hedonic test of flavor and taste. Based on the hedonic test, water content, carbohydrate content, antioxidant capacity, total flavonoid, and viscosity of the selected formula were  F3 (peel (70 g) and flesh (30g)), with water content (30,95%), ash content (0,27%), protein content (0,65%), fat content (0,20%), carbohydrate content (67,93%), antioxidant capacity (164,79 mg AEAC), total flavonoid (0,430 mg/g), viscosity (1333,67 cP) and polish (15,5 cm).